Alien addiction [videorecording (DVD)] - Jackson, Jimi; Sainsbury, Thomas, 1982-; Waaka, Jojo (Gravitas Ventures, 2020)
Life was pretty normal for Riko until two aliens crash land near his house. He welcomes the aliens and develops an epic relationship.